2021
DOI: 10.2319/110620-917.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orthodontic treatment with aligners and fixed appliances on speech:

Abstract: Objectives To evaluate effects of orthodontic treatment with aligners and conventional fixed appliances on production of speech. Materials and Methods This was a parallel, randomized clinical trial. Patients with Angle Class I malocclusion, moderate crowding, and no speech impairment were randomly allocated to two groups: patients with orthodontic aligners (OAs; n = 20; mean age = 23.60 ± 5.65 years) and those with convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
0
11
1
1
Order By: Relevance
“…For the pronunciation difficulties, the results of this study indicated that the patients in the FA group suffered from problems more than those in the CA group during the first six months of treatment. These findings were different from the findings of Melo et al indicated that the orthodontic aligners caused more speech difficulties than the fixed appliances immediately and three days after insertion of the appliances with no significant differences after 30 days of treatment [ 33 ]. These differences could be attributed to the fact that the anchorage control with the labial fixed appliances was maintained using TPAs and Nance buttons in the current study, which could be the leading cause of speech distortions, especially in the initial stages of treatment [ 34 ].…”
Section: Discussioncontrasting
confidence: 88%
“…For the pronunciation difficulties, the results of this study indicated that the patients in the FA group suffered from problems more than those in the CA group during the first six months of treatment. These findings were different from the findings of Melo et al indicated that the orthodontic aligners caused more speech difficulties than the fixed appliances immediately and three days after insertion of the appliances with no significant differences after 30 days of treatment [ 33 ]. These differences could be attributed to the fact that the anchorage control with the labial fixed appliances was maintained using TPAs and Nance buttons in the current study, which could be the leading cause of speech distortions, especially in the initial stages of treatment [ 34 ].…”
Section: Discussioncontrasting
confidence: 88%
“…The ten included studies were conducted in six different countries: Two in Brazil [17,19], three in the USA [14, 15,18], one in Italy [12], Ireland [13], Melbourne [11], Jordan [16], and China [20].…”
Section: Analysis Of Data From Selected Studiesmentioning
confidence: 99%
“…Seven of the studies included patients without extractions in the search [12,13,[15][16][17][18][19] and three studies did not report the absence or presence of extraction [11,14,20].…”
Section: Analysis Of Data From Selected Studiesmentioning
confidence: 99%
“…Já na autoavaliação, os pacientes relataram a percepção de modificação na fala com ambas as abordagens de tratamento. Isso enaltece a importância de o ortodontista alertar os pacientes a respeito de possíveis alterações na fala, deixando claro que são temporárias, independentemente da terapêutica empregada (9).…”
Section: Impactos Na Qualidade De Vidaunclassified